Language Maintenance And Language Shift; A Case Of Kurdish People In Iraq - et. al, Mahabad Salam Sofi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to shed light on language maintenance and language shift among the native speakers of Kurdish in Kurdistan, Iraq. By looking at the participants’ answers concerning their using of Arabic and Kurdish in various domains, and their attitudes toward both languages, the researchers’ objective is to determine the degree and extent of language shift/ maintenance among native speakers of Kurdish. To find out better result the questionnaire is used for 45 participants from different majors and different contexts. The findings of the questioners of the language proficiency show that native speakers’ proficiency level in their language is high. In the same fashion, participants use Kurdish language more than Arabic in most of the contexts with the varied degree. Further, the analysis of the data for language attitude shows that Kurdish people have positive attitudes toward their native language.